The Assessment of the Conjuncture of Labour Market in the European Union Countries - Tauraitė, Viktorija (Lithuanian Journal of Statistics, 2017)
The aim of this article is to find out the factors that influence the conjuncture of labour market in the European Union countries. The aspect of the developed and developing countries is also important in this econometric analysis. The conception of theconjuncture of labour market is described in this article. Moreover, the factors and measuring indicators of these factors are presentedin this analysis, too. The first difference (FD) model is used for econometric analysis of the conjuncture of labour market in the European Union countries. Two hypotheses are formulated in this article, but both are rejected.
Keywords: conjuncture of labour market; labour market demand; labour market supply; first difference model; European Union countries